A lithium iron manganese phosphate composite material and its preparation method and application
Through the use of sodium-yttrium doping and the use of ethylenediamine ferrous sulfate catalyst, a lithium iron manganese phosphate composite material with high electrochemical performance is prepared, which solves the problem of low conductivity and ion migration rate of lithium iron manganese phosphate material and meets the requirements Meet the high specific energy requirements of power batteries.
Patent Information
- Application Number
- CN202411509410.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The conductivity and ion migration rate of the lithium iron manganese phosphate cathode material are low, which cannot fully meet the high specific energy requirements of the power battery.
Using sodium-yttrium doping and ethylenediamine ferrous sulfate as catalyst, lithium iron manganese phosphate composite materials were prepared through hot solvent method and solid-phase ball milling carbothermal method to form graphitized carbon layer and active area to improve the electrochemical performance of the material. .
The electrochemical properties of lithium iron manganese phosphate composite materials are significantly improved, including discharge capacity, capacity retention rate and low-temperature discharge performance.
Smart Images

Figure CN119029192B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium iron manganese phosphate materials, and more specifically, to a lithium iron manganese phosphate composite material and a preparation method and application thereof. Background Art
[0002] As a new type of green energy, lithium batteries are widely used in various fields due to their excellent performance such as high operating voltage, high energy density, long cycle life, low self-discharge, no pollution and good safety performance. With the rise of new energy vehicles and smart device industries, people need efficient and portable energy devices, and lithium batteries have gradually become a research hotspot for scholars. One of the core parts of lithium batteries is the positive electrode material, which directly affects the performance of the battery. At present, common positive electrode materials for lithium batteries include lithium cobalt oxide, lithium manganese oxide, ternary materials (nickel cobalt manganese oxide layered materials, NCM), lithium iron phosphate (LFP), etc.
[0003] Lithium iron phosphate cathode materials have good cyclability, high stability and safety, and low cost, but their specific energy is low and cannot fully meet the growing high specific energy requirements of current power batteries. By doping lithium iron phosphate materials with manganese, the synthesized lithium iron manganese phosphate cathode material has a high platform voltage and high theoretical specific energy, while possessing the advantages of lithium iron phosphate materials, becoming an optimized route for a new type of battery. As an optimized material for lithium iron phosphate, lithium iron manganese phosphate retains the advantages of lithium iron phosphate, but also retains its defects of low conductivity and low ion migration rate. Summary of the invention
[0004] In order to further improve the electrochemical performance of lithium iron manganese phosphate to meet market demand, the present application provides a lithium iron manganese phosphate composite material and a preparation method and application thereof.
[0005] In a first aspect, the present application provides a method for preparing a lithium iron manganese phosphate composite material, using the following technical solution:
[0006] A preparation method of a lithium iron manganese phosphate composite material comprises the following steps: S1, adding a lithium source, a phosphorus source, a manganese source, an iron source, sodium acetate and yttrium phosphate into an ethylene glycol solution in proportion, stirring and dissolving them uniformly, then adding octadecyl dimethyl benzyl ammonium chloride and L-ascorbic acid, adding ammonia water to adjust to neutrality, reacting at 200-220° C. for 10-12 hours, washing and drying to obtain a first precursor; S2, ball-milling the first precursor and a carbon source until the particle size is less than 10 microns, stopping the ball milling, drying to obtain a second precursor; S3, sintering the second precursor at a specific temperature in an argon environment, cooling to room temperature, grinding and passing through a 300-350 mesh sieve to obtain a lithium iron manganese phosphate composite material.
[0007] By adopting the above technical scheme, sodium-yttrium doping is used to perform dual-site doping on lithium iron manganese phosphate, and a first precursor is prepared by a hot solvent method. Sodium-yttrium co-doping is beneficial to particle refinement. At the same time, ethylenediamine ferrous sulfate is used as a catalyst, sucrose and hydroxyethyl cellulose are used as carbon sources, and the first precursor is used to perform a solid phase ball milling carbon thermal method to prepare a lithium iron manganese phosphate composite material. Ethylenediamine ferrous sulfate is converted into ferrous oxide by heating, and ferrous oxide is converted into iron to form a graphitized carbon layer. At the same time, gas is generated by carbonization to form a rough and loose structure, which increases the surface area of the prepared sample, reduces the diffusion distance of Li+, and increases the active area, thereby greatly improving the electrochemical performance of the lithium iron manganese phosphate composite material.
[0008] Preferably, in S1, the lithium source, phosphorus source, manganese source, iron source, sodium acetate and yttrium phosphate have a molar ratio of Li:P:Mn:Fe:Na:Y equal to 5-7:5-6:3-4:2-3:0.1-0.2:0.04-0.06.
[0009] By adopting the above technical solution, the first precursor particles prepared at this ratio are finer.
[0010] Preferably, in S1, the ethylene glycol solution is 13-18 times the total mass of the lithium source, phosphorus source, manganese source, iron source, sodium acetate and yttrium phosphate, and the volume ratio of ethylene glycol to water in the ethylene glycol solution is 1-1.2:1.5-2.
[0011] By adopting the above technical solution, the first precursor prepared with ethylene glycol aqueous solution as solvent has a smaller particle size and a relatively uniform size.
[0012] The molar addition amount of the octadecyl dimethyl benzyl ammonium chloride is 1.5-2 times the total molar amount of Li, P, Mn, Fe, Na, and Y, and the molar addition amount of the L-ascorbic acid is 1-1.2 times the total molar amount of Li, P, Mn, Fe, Na, and Y.
[0013] By adopting the above technical solution, by adding octadecyl dimethyl benzyl ammonium chloride and L-ascorbic acid, the particle size can be reduced, the lithium ion diffusion path can be shortened, and the electrochemical performance of the material can be improved.
[0014] Preferably, in S2, the added amount of the carbon source is 8-12% of the mass of the first precursor.
[0015] By adopting the above technical solution, too much or too little carbon source will affect its electrochemical performance. The lithium iron manganese phosphate composite material prepared with the carbon source addition at this ratio has the best electrochemical performance.
[0016] Preferably, the carbon source consists of sucrose, hydroxyethyl cellulose, and ethylenediamine ferrous sulfate in a mass ratio of 4-7:4-5:1-1.5.
[0017] The order of adding the carbon source is: first add ethylenediamine ferrous sulfate, ball mill for 2-3 hours, then add sucrose, continue ball milling for 3-4 hours, and finally add hydroxyethyl cellulose, and add 8-10% water by weight of hydroxyethyl cellulose, and continue ball milling until the required particle size is reached.
[0018] By adopting the above technical scheme, a first precursor is prepared by a hot solvent method, and then the first precursor and ethylenediamine ferrous sulfate are mixed and ground by a solid phase ball milling method, and then sucrose is added to fully mix the first precursor, ethylenediamine ferrous sulfate, and sucrose, and finally hydroxyethyl cellulose is added for wet grinding, and ethylenediamine ferrous sulfate and sucrose are tightly coated on the surface of the first precursor by hydroxyethyl cellulose, and finally carbonization is performed to obtain a lithium manganese iron phosphate composite material, and a uniform coating layer is obtained to enhance its electrochemical stability.
[0019] Preferably, the specific sintering procedure in S3 is: firstly increase the temperature to 330-380°C at a rate of 5°C / min, sinter for 3-5h, then increase the temperature to 700-850°C at a rate of 3°C / min, and sinter for 6-8h.
[0020] By adopting the above technical solution, the lithium manganese iron phosphate composite material obtained by two-step sintering at low temperature and high temperature has a small crystal size and uniform particle size.
[0021] Preferably, the lithium source includes but is not limited to lithium carbonate, lithium dihydrogen phosphate, dilithium hydrogen phosphate and lithium hydroxide; the manganese source includes but is not limited to manganese carbonate and manganese phosphate; the phosphorus source includes but is not limited to lithium lactate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, iron phosphate and manganese phosphate; the iron source includes but is not limited to ferrous oxide, ferric sulfate, ferric phosphate and ferrous oxalate.
[0022] In a second aspect, the present application provides a lithium iron manganese phosphate composite material obtained by the above-mentioned preparation method.
[0023] In a third aspect, the present application provides an application of a lithium iron manganese phosphate composite material, wherein the lithium iron manganese phosphate composite material is used to prepare a positive electrode material for a lithium ion battery.
[0024] In summary, this application has the following beneficial effects:
[0025] 1. The present application adopts sodium-yttrium doping to perform dual-site doping on lithium iron manganese phosphate and adopts a hot solvent method to prepare a first precursor. Sodium-yttrium co-doping is beneficial to the refinement of particles. At the same time, ethylenediamine ferrous sulfate is used as a catalyst, sucrose and hydroxyethyl cellulose are used as carbon sources, and the first precursor is used to perform a solid phase ball milling carbon thermal method to prepare a lithium iron manganese phosphate composite material. Ethylenediamine ferrous sulfate is converted into ferrous oxide by heating, and ferrous oxide is converted into iron to form a graphitized carbon layer. At the same time, gas is generated by carbonization to form a rough and loose structure, which increases the surface area of the prepared sample and reduces the Li + The diffusion distance is shortened, the active area is increased, and the electrochemical performance of lithium manganese iron phosphate composite materials is greatly improved.
[0026] 2. In the present application, it is preferred to prepare the first precursor by a hot solvent method, and then the first precursor and ethylenediamine ferrous sulfate are mixed and ground by a solid phase ball milling method, and then sucrose is added to fully mix the first precursor, ethylenediamine ferrous sulfate, and sucrose, and finally hydroxyethyl cellulose is added for wet grinding, and ethylenediamine ferrous sulfate and sucrose are tightly coated on the surface of the first precursor by hydroxyethyl cellulose, and finally carbonized to obtain a lithium manganese iron phosphate composite material to obtain a uniform coating layer, reduce the agglomeration of primary particles, make the primary particles evenly aggregate together, and enhance their electrochemical stability.
[0027] 3. The lithium manganese iron phosphate composite material prepared by the preparation method of the present application has greatly improved discharge capacity, high capacity retention rate and strong low-temperature discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the XRD diagram of the lithium iron manganese phosphate composite material prepared in Examples 1-3 of the present application.
[0029] Figure 2 This is a SEM image of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application.
[0030] Figure 3 This is the distribution state of O atoms in the EDS image of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application.
[0031] Figure 4 This is the distribution state of P atoms in the EDS image of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application.
[0032] Figure 5 This is the distribution state of Fe atoms in the EDS image of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application.
[0033] Figure 6 This is the distribution state of Mn atoms in the EDS image of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application.
[0034] Figure 7 This is the distribution state of Na atoms in the EDS image of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application.
[0035] Figure 8 This is the distribution state of the Y atoms in the EDS image of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application.
[0036] Fig. 9 This is the distribution state of C atoms in the EDS image of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application.
[0037] Fig.10 This is the Raman spectrum of the lithium iron manganese phosphate composite material prepared in Example 2 of the present application. DETAILED DESCRIPTION
[0038] The present application is further described in detail below with reference to the embodiments.
[0039] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0040] Example
[0041] Example 1
[0042] A lithium iron manganese phosphate composite material is prepared by the following steps:
[0043] S1, adding lithium source, phosphorus source, manganese source, iron source, sodium acetate and yttrium phosphate to ethylene glycol solution in proportion, stirring and dissolving evenly, then adding octadecyl dimethyl benzyl ammonium chloride and L-ascorbic acid, adding ammonia water to adjust to neutrality, reacting at 200°C for 10h, washing with ethanol and water for 3 times respectively, and drying at 100°C for 18h to obtain the first precursor;
[0044] The lithium source, phosphorus source, manganese source, iron source, sodium acetate, and yttrium phosphate in S1 are in a molar ratio of Li:P:Mn:Fe:Na:Y equal to 5:5:3:2:0.1:0.04;
[0045] The ethylene glycol solution in S1 is 13 times the total mass of the lithium source, phosphorus source, manganese source, iron source, sodium acetate, and yttrium phosphate; the volume ratio of ethylene glycol to water in the ethylene glycol solution is 1:1.5;
[0046] The molar addition amount of the octadecyl dimethyl benzyl ammonium chloride is 1.5 times the total molar amount of Li, P, Mn, Fe, Na, and Y;
[0047] The molar amount of the L-ascorbic acid added is 1 times the total molar amount of Li, P, Mn, Fe, Na and Y.
[0048] S2, mixing the first precursor and the carbon source in a ball mill and ball milling until the particle size is less than 10 μm, stopping the ball milling, and drying at 100° C. for 12 h to obtain a second precursor;
[0049] The amount of the carbon source added in S2 is 8% of the mass of the first precursor;
[0050] The carbon source is composed of sucrose, hydroxyethyl cellulose, and ethylenediamine ferrous sulfate in a mass ratio of 4:4:1;
[0051] The order of adding the carbon source is: first add ethylenediamine ferrous sulfate, ball mill for 2 hours, then add sucrose, continue ball milling for 3 hours, and finally add hydroxyethyl cellulose, and add water with a mass percentage of 8% of the hydroxyethyl cellulose, and continue ball milling until the required particle size is reached.
[0052] S3, under argon environment, the second precursor is added into a tubular calcining furnace, the temperature is first raised to 330°C at a rate of 5°C / min, sintered for 5h, then raised to 700°C at a rate of 3°C / min, sintered for 8h, cooled to room temperature, ground through a 300-mesh sieve, and obtained a lithium iron manganese phosphate composite material.
[0053] Example 2
[0054] A lithium iron manganese phosphate composite material is prepared by the following steps:
[0055] S1, adding lithium source, phosphorus source, manganese source, iron source, sodium acetate and yttrium phosphate to ethylene glycol solution in proportion, stirring and dissolving evenly, then adding octadecyl dimethyl benzyl ammonium chloride and L-ascorbic acid, adding ammonia water to adjust to neutrality, reacting at 210°C for 11h, washing with ethanol and water for 3 times respectively, and drying at 100°C for 18h to obtain the first precursor;
[0056] The lithium source, phosphorus source, manganese source, iron source, sodium acetate, and yttrium phosphate in S1 are in a molar ratio of Li:P:Mn:Fe:Na:Y equal to 6:5.5:3.5:2.5:0.15:0.05;
[0057] The ethylene glycol solution in S1 is 15 times the total mass of the lithium source, phosphorus source, manganese source, iron source, sodium acetate, and yttrium phosphate; the volume ratio of ethylene glycol to water in the ethylene glycol solution is 1.1:1.8;
[0058] The molar addition amount of the octadecyl dimethyl benzyl ammonium chloride is 1.8 times the total molar amount of Li, P, Mn, Fe, Na, and Y;
[0059] The molar amount of the L-ascorbic acid added is 1.1 times the total molar amount of Li, P, Mn, Fe, Na and Y.
[0060] S2, mixing the first precursor and the carbon source in a ball mill and ball milling until the particle size is less than 10 μm, stopping the ball milling, and drying at 100° C. for 12 h to obtain a second precursor;
[0061] The amount of the carbon source added in S2 is 10% of the mass of the first precursor;
[0062] The carbon source is composed of sucrose, hydroxyethyl cellulose, and ethylenediamine ferrous sulfate in a mass ratio of 5.5:4.5:1.3;
[0063] The order of adding the carbon source is: first add ethylenediamine ferrous sulfate, ball mill for 2.5 hours, then add sucrose, continue ball milling for 3.5 hours, and finally add hydroxyethyl cellulose, and add water with a mass percentage of 9% of the hydroxyethyl cellulose, and continue ball milling until the required particle size is reached.
[0064] S3, under argon environment, the second precursor is added into the tubular calcining furnace, the temperature is first raised to 350°C at a rate of 5°C / min, sintered for 4h, then raised to 800°C at a rate of 3°C / min, sintered for 7h, cooled to room temperature, ground through a 300-mesh sieve, and obtained a lithium iron manganese phosphate composite material.
[0065] Example 3
[0066] A lithium iron manganese phosphate composite material is prepared by the following steps:
[0067] S1, adding lithium source, phosphorus source, manganese source, iron source, sodium acetate and yttrium phosphate to ethylene glycol solution in proportion, stirring and dissolving evenly, then adding octadecyl dimethyl benzyl ammonium chloride and L-ascorbic acid, adding ammonia water to adjust to neutrality, reacting at 220°C for 12h, washing with ethanol and water for 3 times respectively, and drying at 100°C for 18h to obtain the first precursor;
[0068] The lithium source, phosphorus source, manganese source, iron source, sodium acetate, and yttrium phosphate in S1 are in a molar ratio of Li:P:Mn:Fe:Na:Y equal to 7:6:4:3:0.2:0.06;
[0069] The ethylene glycol solution in S1 is 18 times the total mass of the lithium source, phosphorus source, manganese source, iron source, sodium acetate, and yttrium phosphate; the volume ratio of ethylene glycol to water in the ethylene glycol solution is 1.2:2;
[0070] The molar amount of the octadecyl dimethyl benzyl ammonium chloride added is twice the total molar amount of Li, P, Mn, Fe, Na, and Y;
[0071] The molar amount of the L-ascorbic acid added is 1.2 times the total molar amount of Li, P, Mn, Fe, Na and Y.
[0072] S2, mixing the first precursor and the carbon source in a ball mill and ball milling until the particle size is less than 10 μm, stopping the ball milling, and drying at 100° C. for 12 h to obtain a second precursor;
[0073] The amount of the carbon source added in S2 is 12% of the mass of the first precursor;
[0074] The carbon source is composed of sucrose, hydroxyethyl cellulose, and ethylenediamine ferrous sulfate in a mass ratio of 7:5:1.5;
[0075] The order of adding the carbon source is: first add ethylenediamine ferrous sulfate, ball mill for 3 hours, then add sucrose, continue ball milling for 4 hours, and finally add hydroxyethyl cellulose, and add water with 10% of the mass of hydroxyethyl cellulose, and continue ball milling until the required particle size is reached.
[0076] S3, under argon environment, the second precursor is added into the tubular calcining furnace, the temperature is first raised to 380°C at a rate of 5°C / min, sintered for 3h, then raised to 850°C at a rate of 3°C / min, sintered for 6h, cooled to room temperature, ground through a 350-mesh sieve, and obtained a lithium iron manganese phosphate composite material.
[0077] Comparative Example
[0078] Comparative Example 1
[0079] The same as Example 2, except that sucrose is used instead of hydroxyethyl cellulose.
[0080] Comparative Example 2
[0081] The same as Example 2, except that ethylenediamine ferrous sulfate is not added.
[0082] Comparative Example 3
[0083] Same as Example 2, except that no sodium acetate was added.
[0084] Comparative Example 4
[0085] The same as Example 2, except that yttrium phosphate is not added.
[0086] Performance testing
[0087] (1) The iron manganese lithium phosphate composite materials prepared in Examples 1-3 were analyzed using an X-ray diffractometer. The results are as follows: Figure 1 shown.
[0088] from Figure 1 It can be seen that the XRD diffraction peaks of the lithium iron manganese phosphate composite materials prepared in Examples 1-3 of the present application are consistent with the standard card of lithium manganese phosphate (JCPDS card number 33-0804), no other impurity diffraction peaks appear, and all diffraction peaks shift to high angles. The reason is that Mn 2+The radius is larger than Fe 2+ , proving that the lithium iron manganese phosphate phase with high purity has been successfully synthesized. The baselines of all diffraction patterns are flat, and there is no amorphous phase. In addition, all diffraction patterns have sharp and obvious diffraction peaks, which indicates that the crystallinity of the lithium iron manganese phosphate composite material is relatively high.
[0089] (2) The microscopic morphology of the iron manganese phosphate lithium composite material prepared in Example 2 was observed using a scanning electron microscope. The results are as follows: Figure 2 The elemental composition of its surface was analyzed using an energy spectrometer, and the results are shown in Figure 3-Figure 9 As shown, Figure 3 represents the distribution state of O atoms, Figure 4 represents the distribution state of P atoms, Figure 5 represents the distribution state of Fe atoms, Figure 6 represents the distribution state of Mn atoms, Figure 7 represents the distribution state of Na atoms, Figure 8 represents the distribution state of Y atoms, Fig. 9 Represents the distribution state of C atoms.
[0090] from Figure 2 It can be seen from the scanning electron microscope image in that the lithium iron manganese phosphate composite material prepared in Example 2 is mostly spherical secondary particles with a rough and loose surface and a diameter of 7-10 microns, which are formed by the close aggregation of primary particles with a diameter between 120-280 nanometers. Figure 3-Figure 9 The energy spectrum analysis results show that the bright spots of O, P, Fe, Mn, Na, Y, and C atoms are evenly distributed, indicating that there is basically no atomic agglomeration in the lithium iron manganese phosphate composite material and the distribution morphology is good.
[0091] (3) The graphitization degree of carbon in the iron manganese lithium phosphate composite material prepared in Example 2 was analyzed using a Raman spectrometer. The results are as follows: Fig.10 shown.
[0092] from Fig.10 It can be seen that the lithium iron manganese phosphate composite material is at 1350cm -1 and 1590cm -1 Obvious characteristic peaks appear at the surface, the P-band represents the stretching vibration peak of the phosphate group, the D-band represents the hybridization peak of disordered graphitic carbon, and the G-band represents the hybridization peak of ordered graphitic carbon, indicating that the carbon coating uniformity of the material is better.
[0093] (4) The lithium iron manganese phosphate composite materials obtained in Examples 1-3 and Comparative Examples 1-4 and the commercially available lithium iron manganese phosphate materials (Zhongke Zhiliang New Energy Materials) in the control group were mixed with a conductive agent and a binder as positive electrode materials, respectively. Battery-grade lithium sheets were used as negative electrode materials, and lithium hexafluorophosphate as the main component was used as the electrolyte to assemble simulated batteries, and relevant performance tests were performed. The initial charge and discharge capacity was tested at 0.1C, and the discharge capacity was tested at 1C, 3C, and 5C in turn. Under the condition of 1C charge and discharge, the capacity retention rate was tested after 500 cycles, and the discharge capacity at 1C was tested in an environment of -25°C. The test results are listed in Table 1:
[0094] Table 1. Electrochemical performance test results
[0095]
[0096] As can be seen from Table 1, the lithium iron manganese phosphate composite materials prepared in Examples 1-3 of the present application have high discharge gram capacity, capacity retention rate and excellent low-temperature discharge performance. Combined with Comparative Examples 1-4, the selection of carbon source, the addition of ethylenediamine ferrous sulfate, and the doping of sodium and yttrium metal elements all have different degrees of influence on the electrochemical properties of the lithium iron manganese phosphate composite materials.
[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a lithium iron manganese phosphate composite material, characterized in that: The following steps are involved: S1, adding lithium source, phosphorus source, manganese source, iron source, sodium acetate and yttrium phosphate to ethylene glycol solution in proportion, stirring and dissolving evenly, then adding octadecyl dimethyl benzyl ammonium chloride and L-ascorbic acid, adding ammonia water to adjust to neutrality, reacting at 200-220°C for 10-12h, washing and drying to obtain a first precursor; S2, ball-milling the first precursor and carbon source until the particle size is less than 10 microns, stopping ball milling, drying, and obtaining a second precursor, wherein the carbon source is sucrose, hydroxyethyl cellulose, and ethylenediamine The ferrous sulfate is composed in a mass ratio of 4-7:4-5:1-1.5, and the order of adding the carbon source is: first add ethylenediamine ferrous sulfate, ball mill for 2-3 hours, then add sucrose, continue ball milling for 3-4 hours, and finally add hydroxyethyl cellulose, and add 8-10% water by mass of hydroxyethyl cellulose, and continue ball milling until the required particle size is reached; S3, in an argon environment, sinter the second precursor at a specific temperature, cool to room temperature, and grind through a 300-350 mesh sieve to obtain a lithium iron manganese phosphate composite material.
2. The method for preparing a lithium iron manganese phosphate composite material according to claim 1, characterized in that: In S1, the lithium source, phosphorus source, manganese source, iron source, sodium acetate, and yttrium phosphate have a molar ratio of Li:P:Mn:Fe:Na:Y equal to 5-7:5-6:3-4:2-3:0.1-0.2:0.04-0.
06.
3. The method for preparing a lithium iron manganese phosphate composite material according to claim 2, characterized in that: In S1, the ethylene glycol solution is 13-18 times the total mass of the lithium source, phosphorus source, manganese source, iron source, sodium acetate and yttrium phosphate, and the volume ratio of ethylene glycol to water in the ethylene glycol solution is 1-1.2:1.5-2.
4. The method for preparing a lithium iron manganese phosphate composite material according to claim 2, characterized in that: The molar addition amount of the octadecyl dimethyl benzyl ammonium chloride is 1.5-2 times the total molar amount of Li, P, Mn, Fe, Na, and Y, and the molar addition amount of the L-ascorbic acid is 1-1.2 times the total molar amount of Li, P, Mn, Fe, Na, and Y.
5. The method for preparing a lithium iron manganese phosphate composite material according to claim 1, characterized in that: In S2, the added amount of the carbon source is 8-12% of the mass of the first precursor.
6. The method for preparing a lithium iron manganese phosphate composite material according to claim 1, characterized in that: The specific sintering procedure in S3 is: firstly, the temperature is raised to 330-380°C at a rate of 5°C / min, and sintered for 3-5h, and then the temperature is raised to 700-850°C at a rate of 3°C / min, and sintered for 6-8h.
7. A lithium iron manganese phosphate composite material, characterized in that: Obtained by the preparation method described in any one of claims 1 to 6.
8. An application of a lithium iron manganese phosphate composite material, characterized in that: The lithium iron manganese phosphate composite material according to claim 7 is used to prepare the positive electrode material of a lithium ion battery.
Citation Information
Patent Citations
Method for producing carbon coated nano stage lithium iron phosphate by precipitation
CN101393982A
High-performance lithium manganese iron phosphate material as well as preparation method and application thereof
CN118472196A